Analisis Kinerja Jaringan Menggunakan Metode PCQ pada Jaringan Internet Kelurahan Butuh - Andika Wahyu Kurniawan; Rissal Efendi (LPPM STIKOM Tunas Bangsa, 2024)
The aim of this research is to improve and analyze internet network performance by applying the PCQ (Per Connection Queue) method in the bandwidth management system. The PCQ (Per Connection Queuing) method is a network traffic management technique that allocates bandwidth fairly to each active connection. This method allows network administrators to control network traffic and prioritize low-bandwidth connections. The PCQ method is used to overcome problems that often occur in internet network performance, such as unfair distribution of bandwidth. In analyzing computer network performance using the PCQ method, research is carried out to measure network performance using various parameters such as throughput, delay, jitter, packet loss. This research often compares network performance with and without using the PCQ method, as well as comparisons with other network traffic management methods. Using the PCQ method can fix problems that often occur in internet network performance which has an imbalance in bandwidth usage between one network user and another. The results of this research can be concluded that the use of the PCQ method greatly influences network performance for the better due to the distribution of bandwidth evenly. For this reason, this research is an important contribution in improving bandwidth management that is more effective and efficient